Working on the thresholds of memory and silence: reflections on the praxis of the Legacies of Apartheid Wars Project - Edlmann, Theresa (University of the Free State, 2015)
Just as stories about the past are constructed in particular ways, so too are silences about historical events. Silences about what happened in the past are catalysed by a range of factors including expedience, fear, perceptions of threat, a need to protect, political amnesia, trauma and moral injury. Historical silences are constructed within social spaces and in people’s own accounts of their personal histories and identities. Silences are thus both personal and relational constructs that do not remain static, but rather shift and evolve, and can be disrupted. This article reflects on work conducted by the Legacies of Apartheid Wars Project between 2012 and 2014 at Rhodes University. The aim of these reflections is to explore the theoretical implications of work that sought to intervene in realms of silence and constrained memory, and invite public dialogical engagements with the past. The aim of these engagements was to acknowledge the complexities of apartheid’s legacies and some of the silences enfolded in those complexities, cognisant of the dynamic relationship between speaking and silence in how work of this nature engages with contested political, social and cultural terrains. The work of the Legacies of Apartheid Wars Project could, therefore, be said to comprise memory activism in the midst of ongoing contestation regarding how to make meaning of both the past and the present in the Southern African context.
Keywords: Apartheid; War; Silence; Memory; Legacies of Apartheid Wars Project